DIABETIC NEPHROPATHY AN OBVIOUS COMPLICATION IN LONG TERM TYPE 1 DIABETES MELLITUS: A CASE STUDY - Islam Mohammad, Jahidul; Chigurupati, Sridevi; Othman, Azli Shahril; Zahid Iqbal, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Most overwhelming complications of Type 1 diabetes mellitus patients are responsible for complications related to the microvascular system most likely with kidney. In the kidney, hyperglycemia induced microangiopathy resulting not only thickening of the glomerular capillary basement membrane but also to the proliferation of the mesangial matrix and solidifying of the tubular basement membrane. Several biochemical and pathological, factors are concerned for the development of diabetic renal microangiopathy. These include the glomerular hyperperfusion and hyperfiltration, transformed morphology of podocytes accompanies these basement membrane modifications, Type IV collagen augmented synthesis following the hyperglycemia, and increased expression of tissue matrix metalloproteinase. The aim of this case review is to highlight the recent advances in understanding the pathogenesis, diagnosis, the overview and the potential renoprotective therapeutic agents that would prevent the development or the progression of diabetic nephropathy.